Partial Discharge Detection using UHF Sensor on High Voltage Equipment - Asmat, Muhammad Asyraf; Abd Rahman, Rahisham (Evolution in Electrical and Electronic Engineering, 2024)
High voltage transmission is essential for efficient energy transfer in power systems, relying on key components like transformers and Gas Insulated Switchgear (GIS). Detecting partial discharge (PD) is vital to prevent insulation failure and ensure system reliability. This study addresses the limitations of traditional PD detection methods, which are often intrusive and noisy, by employing Ultra-High Frequency (UHF) sensors for sensitive, non-invasive detection. The primary objectives were to use UHF sensors to study partial discharges in high-voltage equipment, identify insulation defects in laboratory settings, and analyze PD signals. HVAC tests were conducted to replicate PD events, with electromagnetic radiation measured using UHF antennas. The findings demonstrated that UHF sensors effectively capture PD-related electromagnetic signals, offering superior sensitivity and accuracy. This non-invasive method enhances the reliability and lifespan of high-voltage equipment by enabling early detection of insulation flaws, thereby improving maintenance and operational strategies for more consistent power delivery.